2019
DOI: 10.5539/elt.v12n8p95
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Play Center Activities of Early Childhood Education in China

Abstract: As one typical form of play, play center activities are commonly used in early childhood education programs in China. This study used the Activities Sub-scale of the Chinese Early Childhood Environment Rating Scale (CECERS) to measure the quality of the play center activities in K2 (4-5 years old) classroom, which based on a stratified random selection of 48 classrooms in Guangdong Province in China. Results found that the overall quality of play center activities was slightly below qualified (5 points), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…According to the results obtained the access to digital libraries in Pakistan is weak. While research from Liu, et al, (2019), reported that digital library access in China was available in more than 80% universities making it easier for students to access digital libraries at their homes. Supporting the statement, Bhayo et al, (2018) wrote that digital library access is available to all the students in various provinces of China except for a few new universities where developments are taking place.…”
Section: Critical Comparison Of Results With Chinamentioning
confidence: 99%
See 2 more Smart Citations
“…According to the results obtained the access to digital libraries in Pakistan is weak. While research from Liu, et al, (2019), reported that digital library access in China was available in more than 80% universities making it easier for students to access digital libraries at their homes. Supporting the statement, Bhayo et al, (2018) wrote that digital library access is available to all the students in various provinces of China except for a few new universities where developments are taking place.…”
Section: Critical Comparison Of Results With Chinamentioning
confidence: 99%
“…The governance of HEIs in China is done by the State and local Councils, which monitors the facilities provided in each department. According to Liu, Hu and Huang (2019), the HEIs in China focus on many parameters in improving quality of education and some of them include, quality of work distribution, and increasing accessibility for the students. Bhayo et al, (2018) reported that the number of PhD faculty members in China have increased in the order of thousands in the last 10 years because of the special focus on increasing the quality of their classroom environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation